Behavior and analytical investigation of assembled connection between steel beam and concrete encased CFST column. (April 2020) - Wang, Wanqian; Wang, Jingfeng; Guo, Lei; Guo, Xiang; Liu, Xiaoxian
Abstract: Concrete encased CFST (CECFST) column is a composite member consisted of outer encased concrete and inner CFST. Currently, a cast-in-place connection between a CECFST column and a reinforcement concrete beam is generally employed in engineering practice due to the outer encased concrete hinders the application of assembled connection, and the steel beam is usually connected to the CECFST column by on-site welding. In this paper, a novel on-site assembled connection between a CECFST column and a steel beam was proposed. In considering various material models and complex contacts, a FE model for this type of joint was established and verified. Further, parametric analyses of the assembled connections to concrete encased CFST columns were conducted to analyze the structural behavior. More importantly, an extended component model was developed to cover the feature of CECFST column focusing on the initial stiffness and moment resistance of the assembled connection. The load transfer mechanism for bolt in tension and beam flange in compression were considered in the modelling for evaluating the stiffness and strength of column wall in tension and in compression, respectively. The numerical results from the parametric analyses coincided well with the predicted results. The numerical and analytical results declared that this novel assembled connection between the CECFST column and steel beam performed favorable structural behavior and could be employed in assembled structures with CECFST columns.